The ultimate guide to weight training for gymnastics - Price, Robert G., ....- (2006)
"The Ultimate Guide to Weight Training for Gymnastics is the most comprehensive and up-to-date gymnastics-specific training guide in the world today. It contains descriptions and photographs of nearly 100 of the most effective weight training, flexibility, and abdominal exercises used by athletes worldwide. This book features year-round gymnastics-specific weight-training programs guaranteed to improve your performance and get you results. No other gymnastics book to date has been so well designed, so easy to use, and so committed to weight training. This book will have gymnasts increasing flexibility, strength, and agility enabling the highest level of performance. By following this program you will improve everything from compositions to releases with better overall execution. Both beginners and advanced athletes and weight trainers can follow this book and utilize its programs. From recreational to professional, thousands of athletes all over the world are already benefiting from this book and its techniques, and now you can too!"
Maximize your athletic potential! - in-season and off-season sport-specific programs designed to: increase strength and flexibility, eliminate fatigue, and prevent injuries - Gymnastiek.
Keywords: Turnen ; krachttraining